Possible trace fossils of putative termite origin in the Lower Jurassic (Karoo Supergroup) of South Africa and Lesotho - E.M. Bordy; A.J. Bumby; O. Catuneanu; P.G. Eriksson (South African Journal of Science)
Complex structures in the sandstones of the Lower Jurassic aeolian Clarens Formation (Karoo Supergroup) are found at numerous localities throughout southern Africa, and can be assigned to five distinct architectural groups: (1) up to 3.3-m high, free-standing, slab-shaped forms of bioturbated sandstones with elliptical bases, orientated buttresses and an interconnecting large burrow system; (2) up to 1.2-m high, free-standing, irregular forms of bioturbated sandstones with 2-cm to 4-cm thick, massive walls, empty chambers and vertical shafts; (3) about 0.15-m to 0.25-m high, mainly bulbous, multiple forms with thin walls (larger than 2 cm), hollow chambers with internal pillars and bridges; (4) about 0.15-m to 0.2-m (maximum 1-m) high, free-standing forms of aggregated solitary spheres associated with massive horizontal, orientated capsules or tubes, and meniscate tubes; and (5) about 5 cmin diameter, ovoid forms with weak internal shelving in a close-fitting cavity. Based on size, wall thickness, orientation and the presence of internal chambers, these complex structures are tentatively interpreted as ichnofossils of an Early Jurassic social organism; the different architectures are reflective of the different behaviours of more than one species, the history of structural change in architectural forms (ontogenetic series) or an architectural adaptation to local palaeoclimatic variability. While exact modern equivalents are unknown, some of these ichnofossils are comparable to nests (or parts of nests) constructed by extant termites, and thus these Jurassic structures are very tentatively interpreted here as having been made by a soil-dwelling social organism, probably of termite origin. This southern African discovery, along with reported Triassic and Jurassic termite ichnofossils from North America, supports previous hypotheses that sociality in insects, particularity in termites, likely evolved prior to the Pangea breakup in the Early Mesozoic.